TINJAUAN YURIDIS TENTANG PEMBATALAN PERKAWINAN DALAM PUTUSAN PERKARA CERAI GUGAT DAN AKIBAT HUKUMNYA (STUDI NO 2690/pdt. G /2016/PA. TGRS DI PENGADILAN AGAMA TIGARAKSA) - Bulqoynie Akmal Habibullah (Dinamika, 2020)
ABSTRACTThis study discusses the cancellation of marriage at the Tigaraksa Religious Court in Tangerang Regency. Law No. 1 of 1974 regulates marital problems with great care and detail. marriages are carried out on the basis of the willingness of the parties concerned, What is the position of their assets in the event of a divorce with a decision to cancel the marriage by the court? Second, what is the status of a child born as a result of the annulment of a marriage by a religious court based on decision No. 2690 / Pdt.G / 2016 / PA. Tgrs ?. This study uses normative legal research, Law No. 1 of 1974 Article 37 only regulates shared assets as a result of divorce. Whereas for annulled marriages, in the practice of the Religious Courts there has not yet been found any rules regarding the distribution of joint property from annulled marriages, it is clear that the status of children born from marriages that are null and void is still called legitimate children, Article 76 of the Compilation of Islamic Law states that marriages having a cancellation will not break the legal relationship between the child and his parent.Keywords: Marriage Cancellation, Legal Consequences, Asset, Child Status ABSTRAKPenelitian ini membahas tentang pembatalan perkawinan di Pengadilan Agama Tigaraksa Kabupaten Tangerang. Undang-Undang No. 1 Tahun 1974 mengatur masalah perkawinan dengan amat teliti dan terperinci. perkawinan dilaksanakan atas dasar kerelaan pihak-pihak yang bersangkutan,  Bagaimanakah kedudukan harta mereka dengan adanya cerai gugat dengan putusan pembatalan perkawinan oleh pengadilan? Kedua, Bagaimanakah status anak yang dilahirkan akibat pembatalan perkawinan oleh pengadilan agama berdasarkan putusan Nomor 2690/Pdt.G/2016/PA. Tgrs?. Penelitian ini menggunakan penelitian hukum normatif, Undang-Undang Nomor 1 Tahun 1974 Pasal 37 hanya mengatur tentang harta bersama sebagai akibat dari perceraian saja. Sedangkan terhadap perkawinan yang dibatalkan, dalam praktek Pengadilan Agama belum ditemukan adanya aturan mengenai pembagian harta bersama dari perkawinan yang dibatalkan, jelas bahwa status anak-anak yang dilahirkan dari perkawinan yang batal masih disebut sebagai anak sah, Pasal 76 Kompilasi Hukum Islam menyatakan bahwa perkawinan yang mengalami pembatalan tidak akan memutuskan hubungan hukum antara anak dengan orang tuanya.Kata Kunci : Pembatalan Perkawinan, Akibat Hukum, Kedudukan Harta, Status Anak